2018
DOI: 10.1177/1557988318758786
|View full text |Cite
|
Sign up to set email alerts
|

Power Up for Health—Participants’ Perspectives on an Adaptation of the National Diabetes Prevention Program to Engage Men

Abstract: The National Diabetes Prevention Program (NDPP) has been effectively translated to various community and clinical settings; however, regardless of setting, enrollment among men and lower-income populations is low. This study presents participant perspectives on Power Up for Health, a novel NDPP pilot adaption for men residing in low-income communities in New York City. We conducted nine interviews and one focus group with seven participants after the program ended. Interview and focus group participants had po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…These preliminary data presented here and in the related publications ( Gary-Webb et al, 2018 ; Realmuto et al, 2018 ) form an important basis for a more rigorous clinical trial of a diabetes prevention program for men from disadvantaged, urban neighborhoods. Many lessons were learned regarding the training and support of coaches, male-oriented program materials and activities, and recruitment strategies.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…These preliminary data presented here and in the related publications ( Gary-Webb et al, 2018 ; Realmuto et al, 2018 ) form an important basis for a more rigorous clinical trial of a diabetes prevention program for men from disadvantaged, urban neighborhoods. Many lessons were learned regarding the training and support of coaches, male-oriented program materials and activities, and recruitment strategies.…”
Section: Discussionmentioning
confidence: 56%
“…Many lessons were learned regarding the training and support of coaches, male-oriented program materials and activities, and recruitment strategies. Coaches, participants, and the Advisory Panel suggested the positive addition of group physical activity at the time of each session; this advice is supported by recent research reports concerning African American men ( Dean et al, 2016 ) and the Power Up for Health qualitative data reported ( Realmuto et al, 2018 ). More research is needed on enhanced recruitment strategies for men from disadvantaged neighborhoods.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This manuscript describes the critical relationship the study team developed with the Advisory Panel, experts in men’s health, and male community leaders, who guided us in the process of adapting and implementing the program named by them Power Up for Health . The outcomes of the pilot study, as well as qualitative perspectives of participants, are described in companion papers in this journal ( Realmuto et al, 2018 ; Walker et al, 2018 ).…”
mentioning
confidence: 99%